Electrolyte Engineering with Asymmetric Spatial Shielding Effect for Aqueous Zinc Batteries - Cong, Jianlong; Hu, Zuyang; Hu, Le; Li, Tongjiang; Ji, Haijin; Long, Zihan; Fan, Yuxin; Wen, Zhipeng; Lin, Yu‐Chang; Xu, Henghui; Li, Zhen; Li, Shunning; et al. (Advanced functional materials, 2025)
The electrochemical instability of electrode/electrolyte interface and aqueous electrolyte collectively brings technical barriers, such as side reactions like hydrogen evolution and corrosion, as well as zinc dendrites, which hinder the practical application of aqueous zinc batteries. Here, an electrolyte engineering strategy is proposed with asymmetric spatial shielding effect by employing the molecules with asymmetric spatial structure as a cosolvent. Such molecule contains small methyl group and large cyclopentyl group to balance migration capability and shielding volume, which can not only promote the solvation structure of Zn2+ containing more anions and solid electrolyte interface derived from abundant anions but also rapidly and effectively adsorb on the surface of Zn anode to remodel the electric double layer. This strategy alleviates hydrogen evolution and corrosion while achieving dendrite‐free Zn deposition. Consequently, the Zn/I2 cell can operate stably at 2 A g−1 for 30 000 cycles over 180 days, with a capacity retention of 79.8%. Despite featuring a cathode areal capacity of 4.74 mAh cm−2 and an N/P ratio of 2.5, the Zn/NH4V4O10 cell still achieves an impressive capacity retention of 88.8% at 0.5 A g−1 for 200 cycles, demonstrating a significant potential for practical application. This work proposes an electrolyte engineering strategy with asymmetric spatial shielding effect that not only simultaneously promotes the solvation structure of Zn2+ containing more anions and remodels the electric double layer but also highlights the balance between migration capability and shielding effect. Hence, excellent electrochemical performances with long cycle life, wide temperature range, and high loading capacity are attained for aqueous zinc batteries.